Transport and removal of a solvent in porous media in the presence of bitumen, a highly viscous solute. (29th June 2017) - Panda, Siddhant; Pal, Krupal; Merzara, Sumeet; Gray, Murray R.; Liu, Qi; Choi, Phillip
Highlights: Drying of a solvent along with a highly viscous solute in porous media was studied. Duration of solvent removal stage increased with increasing solute concentration. Vapor pressure, capillary transport of solution and pore blockage were investigated. High solute concentration reduced capillary transport and thereby solvent recovery. Abstract: Removal of solvent from the gangue generated by an oil sands solvent extraction process is essentially a process of solution transport in a porous medium with a highly viscous solute (left over bitumen of a completed extraction process or residual bitumen) at low concentrations. The solvent usually has much higher vapor pressure and lower viscosity than the residual bitumen. The concentrations of the residual bitumen are typically in the range of 0.6–2.4 wt% while those of the solvent (cyclohexane) is 8–12 wt% at the start of the drying process to remove the solvent. Drying of gangue was carried out for 2 h under ambient conditions using petri dishes with bed heights of 0.6, 1.0 and 1.4 cm. A typical drying curve (i.e., cumulative volatiles mass loss versus time) shows two distinct drying stages in which the first stage is the fast evaporation of cyclohexane (99% by weight removal) followed by a stage in which slow evaporation of water is observed. The residual bitumen was observed, unexpectedly, to migrate to the top surface of the porous media with cyclohexane via capillary transport and accumulate there in the first stage of drying. The rate of removal of cyclohexane decreased with increasing residual bitumen content. Consequently, duration of the fast cyclohexane removal stage from the gangue sample containing 2.4 wt% bitumen was 1.5 times longer than that of the 0.6 wt% bitumen gangue sample, when the initial cyclohexane concentration was 12 wt%; it was 1.2 times longer when the initial cyclohexane concentration was 8 wt%. Our studies reveal that poor capillary transport of solution in porous media at higher bitumen concentrations to be the most likely cause of slower drying rather than vapor pressure lowering of bulk solution and pores blockage. The cause is similar to previous reports in literature with the solute being salt in salt-water solution.